Casting material made of copper-zinc alloy, method for producing cast product, and casting

By adding silicon and phosphorus to the copper-zinc alloy, adjusting the β-phase ratio and cooling rate, forming a specific microstructure, the problem of poor machining under low lead content is solved, and excellent machining and polishability are achieved, while reducing the risk of environmental pollution.

CN119585454APending Publication Date: 2025-03-07WIELAND WERKE AG
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380055678.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-11
Filing Date
2023-08-02
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing copper-zinc alloys contain harmful lead, which leads to environmental pollution and health risks, and it is difficult to maintain good mechanical processing under low lead content.

Method used

By adding silicon (Si) and phosphorus (P) to the copper-zinc alloy, adjusting the volume ratio of the β phase, combined with appropriate cooling rates, a microstructure composed of α phase, β phase and phosphide particles is formed to improve machining and polishability.

Benefits of technology

The excellent mechanical processing, good mechanical characteristics and small grain size of copper-zinc alloys under low lead content are achieved, reducing the risk of environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005253837180000081
    Figure BDA0005253837180000081
  • Figure BDA0005253837180000091
    Figure BDA0005253837180000091
  • Figure BDA0005253837180000092
    Figure BDA0005253837180000092
Patent Text Reader

Abstract

The invention relates to a casting material made of a copper-zinc alloy having the following components in% by weight: Cu: 58.0% to 66.0%, Si: 0.15% to 1.2%, P: 0.20% to 0.38%, Sn: optionally at most 0.5%, Al: optionally at most 0.05%, Fe: optionally at most 0.3%, Ni: optionally at most 0.3%, Pb: optionally at most 0.25%, Bi: optionally at most 0.1%, Te, Se, In, each optionally at most 0.1%, B: optionally at most 0.01%, and the balance of Zn and inevitable impurities, wherein the proportion of the inevitable impurities is less than 0.2% by weight. The alloy has a structure of an alpha phase, a beta phase and phosphide particles. The proportion of the beta phase in the sum of the alpha and beta phases is at least 20% by volume and at most 70% by volume. Silicon exists in two forms of an alpha phase and a beta phase. In an area of 21000 [mu] m2, there are 20 to 300 phosphide particles having an equivalent diameter of 0.5 [mu] m to 1 [mu] m, 30 to 120 phosphide particles having an equivalent diameter of 1 [mu] m to 2 [mu] m, and 20 to 100 phosphide particles having an equivalent diameter of 2 [mu] m to 5 [mu] m. The ratio of the beta phase and the ratio of Si and P are selected such that the condition 92.7249-0.473254 [beta]-80.6378 [Si]-142.65 [P] + 279.309 [Si] [P] < 40 is satisfied, where [beta] represents the ratio of the beta phase in vol%, [Si] represents the ratio of silicon in wt%, and [P] represents the ratio of phosphorus in wt%.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The invention relates to a casting material consisting of a copper-zinc alloy, to a method for producing a casting product, and to a casting.

[0002] Copper-zinc casting materials (also called "casting alloys") consisting of α-phase and β-phase and having about 1% by weight of lead, such as CuZn39Pb1Al-B (CB757S), have excellent castability, very good machinability and also good polishability. Leaded copper-zinc casting alloys are used in a variety of applications in the sanitary sector, in particular, for taps and fittings in the drinking water industry.

[0003] The basis for the positive effect of lead in copper-zinc alloys is that the lead is in the elemental form of particles in the microstructure, and these particles act as a chip agent. During machining, the lead is in the form of a liquid phase due to the significant local deformation in the workpiece and the resulting local temperature increase. Since lead cannot absorb stresses in the liquid state, this leads to stress concentrations in the load-bearing, weakened matrix, which therefore leads to a greater tendency for chip breakage. In addition, during machining, lead is also incorporated in the friction layer between the material and the workpiece, thus leading to effective lubrication and, therefore, to a reduction in friction and wear. In addition, it is known that lead in copper-zinc alloys leads to a significant grain refinement. This is advantageous for polishability, especially in the case of cast materials. In addition, lead is inexpensive.

[0004] However, lead damages the environment. Lead accumulates in the human body when ingested in very small amounts and can cause damage to health. Therefore, the European Union, the United States, China and other countries have further reduced the restrictions on copper alloys, and there is a drive to replace leaded brass with reduced lead or lead-free machinable copper alloys. Restrictions are defined in EU directives, such as Directive 2011 / 65 / EU (RoHS), which stipulates 1000 ppm (0.1%) of Pb as an upper limit. In order to ensure good machinability of the material even at such low lead contents, various alloying elements have been proposed as substitutes for lead.

[0005] It is known from numerous publications that bismuth (Bi) can be used as a substitute for lead in order to improve machinability. In order to mitigate the problem of Bi filming along grain boundaries and the associated tendency to stress cracking and thermal cracking, it is proposed to also contain other elements in the alloy. In this regard, reference is made in particular to KR 10 0 555 854 B1, KR 10 2006 096877 A, JP 2005 290475 A, JP 2014 122 427 A and JP 2006 083 443 A. However, Bi is undesirable because it is firstly a low availability metal that exists only in a limited volume and secondly leads to hot brittleness in the material cycle of copper alloys.

[0006] Furthermore, document EP 2 194 150 B1 discloses a copper-zinc alloy containing 0.1% to 1.5% by weight of Si, 0.03% to 0.4% by weight of Al, 0.01% to 0.36% by weight of P, 0.05% to 0.5% by weight of Sn, and 0.001% to 0.05% by weight of rare earths. The alloy has good machinability due to the formation of α, β and possibly γ microstructures. The Al content leads to the formation of unwanted aluminum phosphides. Although the γ phase and aluminum phosphides improve the formation of chips, they deteriorate the service life of the tool. In addition, the proportion of rare earths may lead to microstructural embrittlement. The alloy is used for castings and hot pressed parts.

[0007] Document EP 3 992 321 A1 also describes the replacement of lead with phosphorus, which forms brittle phosphides in the alloy, for a casting alloy with 58.5% to 65.0% by weight of Cu, 0.40% to 1.40% by weight of Si, 0.003% to 0.19% by weight of P, 0.002% to 0.25% by weight of Pb, the remainder: zinc and other optional elements. The addition of 0.003% to 0.19% by weight of P for phosphide formation and 0.4% to 1.4% by weight of Si for hardening the α- and β-crystallites results in a casting material with good machinability.

[0008] The object of the present invention is to provide a casting material consisting of a copper-zinc alloy having excellent machinability, good mechanical properties, a small grain size and therefore good polishability, a low tendency to form cavities and a minimum content of alloy components of environmental concern. Another object of the present invention is to specify a method for producing a cast product and a casting.

[0009] The invention is characterized by the features of claim 1 with respect to the casting material consisting of a copper-zinc alloy and by the features of claim 7 with respect to the production method. Further dependent claims relate to advantageous embodiments and developments of the invention.

[0010] The present invention relates to a casting material consisting of a copper-zinc alloy having the following components in wt. %:

[0011] Cu: 58.0% to 66.0%,

[0012] Si: 0.15% to 1.2%,

[0013] P: 0.20% to 0.38%,

[0014] Sn: optionally, up to 0.5%,

[0015] Al: optionally, up to 0.05%,

[0016] Fe: optionally, up to 0.3%,

[0017] Ni: optionally, up to 0.3%,

[0018] Pb: optionally, up to 0.25%, preferably up to 0.10%,

[0019] Bi: optionally, up to 0.1%,

[0020] Te, Se, In: each optionally, up to 0.1%,

[0021] B: optionally, up to 0.01%,

[0022] Balance: Zn and unavoidable impurities,

[0023] The proportion of unavoidable impurities is less than 0.2% by weight. The alloy has a microstructure consisting of α phase, β phase and phosphide particles. The phosphide particles contain or are preferably phosphides containing copper and / or zinc. The proportion of β phase in the sum of α phase and β phase is at least 20% by volume, preferably at least 40% by volume, and not more than 70% by volume, preferably not more than 60% by volume. Silicon is present in both the α phase and the β phase. At 21000 μm 2 In an area of ​​20 to 300 phosphide particles with an equivalent diameter of 0.5 μm to 1 μm, 30 to 120 phosphide particles with an equivalent diameter of 1 μm to 2 μm, and 20 to 100 phosphide particles with an equivalent diameter of 2 μm to 5 μm are present. The volume proportion of the β phase and the proportion of Si and P are selected so that the alloy satisfies the following conditions

[0024] 92.7249-0.473254·[β]-80.6378·[Si]-142.65·[P]+279.309·[Si]·[P]<40

[0025] Here, [β] represents the proportion of the β phase in % by volume, [Si] represents the proportion of silicon in % by weight, and [P] represents the proportion of phosphorus in % by weight.

[0026] The invention is based on the consideration of reducing the proportion of Pb in the copper-zinc alloy as much as possible without deteriorating the machinability of the material. For this purpose, Si and P are added to the alloy in particular, and the volume proportion of the β phase is adjusted in order firstly to produce favorable machining characteristics and secondly to refine the casting microstructure of the original basic matrix composed of the β phase. In addition, the process regime in the casting operation is selected in order to produce the desired characteristics.

[0027] A small β grain size is advantageous for good polishability. Therefore, the β phase must be in the form of fine grains in the cast state. It has been surprisingly found that with increasing P content, a significant grain refinement of the casting microstructure of the original base matrix consisting of the β phase component occurs. In order to achieve sufficient grain refinement of the casting microstructure, an addition of at least 0.20% by weight of P is necessary. This is similar to the effect of 1 to 3% by weight of Pb on the grain refinement of α-β-brass. In the primary crystallization of the β crystallites, the residual melt becomes rich in P and thus leads to a subdivision of the β phase and thus to a grain refinement. Solidification forms a eutectic consisting of phosphides and β phase. In addition to the grain refinement of the base matrix consisting of the β phase, a grain refinement of the α crystallites is observed.

[0028] In the case of a P content of at least 0.20% by weight, phosphide particles are present in the cast material in both the α phase and the β phase. The alloy preferably contains at least 0.22% by weight of P. In the case of a P content of more than 0.38% by weight, coarse phosphides are formed in the cast state, because the individual phosphides condense and form long network forms. These coarse phosphides wet the grain boundaries and reduce the ductility. For use as mechanical parts, for example as drinking water valves or connectors, the material needs to have a high strength corresponding to the high hardness.

[0029] However, even in the case of P contents below 0.38% by weight, coarse undesirable phosphides may also appear when the cooling rate is too low in the casting of the alloy, for example in the case of casting into a fixed mold. For example, the necessary high cooling rate is achieved in the Tammann casting of a small 25x 55x 160 mm block into a steel mold. This achieves the effect that, in the case of P contents of 0.20% to 0.38% by weight, the phosphide particles are in a spherical and finely distributed form in the microstructure even in the cast state. These act as separation sites in machining and promote chip breakage. In order to properly adjust the phosphide particles, the cooling rate during solidification must be at least 20°C per minute (°C / min), preferably at least 30°C per minute, and at most 60°C per minute, preferably at most 50°C per minute, in the temperature range from 550°C to 350°C. Therefore, the distribution of phosphides and the grain size of the β phase are determined not only by the chemical composition of the alloy, but also by the conditions in the casting operation. The characteristics of the phosphides in the cast state are therefore similar to the fingerprint left on the product by a specific process recipe. The distribution of phosphides in the cast state can be characterized as follows: 2In an area of ​​1000 square meters, there are 20 to 300 phosphide particles with an equivalent diameter of 0.5 μm to 1 μm, 30 to 120 phosphide particles with an equivalent diameter of 1 μm to 2 μm, and 20 to 100 phosphide particles with an equivalent diameter of 2 μm to 5 μm. The equivalent diameter of the phosphide particles refers to the diameter of a circle with the same area as the phosphide particles. The main part of the phosphide particles with an equivalent diameter of at least 0.5 μm has an equivalent diameter of not more than 2 μm. Taking into account the cooling conditions, the alloy is also suitable for continuous casting and forming casting, for example in the form of sand casting or model casting.

[0030] The brittle microstructural component is advantageous for the machinability of the material, which acts as a separation site in the machining operation and thus promotes chip fracture. The β phase is brittle and promotes machinability. An increase in the proportion of the β phase can be achieved by an increase in the Zn content and / or by including silicon in the alloy, because silicon stabilizes the β phase. It has also been found that when the ductility of the α phase is reduced, it is advantageous for good machinability. This can be achieved by alloying and incorporating silicon into the α phase, and by finely distributed phosphides in the α phase. Therefore, the Si content in the alloy must be at least 0.15% by weight. The above-mentioned phosphide particles are particles that act as separation sites and promote chip fracture in machining. A P content of at least 0.20% by weight not only improves machinability, but also particularly refines the particles. In addition, an optional small portion of Pb has a favorable effect on machinability.

[0031] Therefore, the machinability of the material is determined by the combined selection of the parameters of the β phase, Si and P, and optionally a small proportion of Pb. In the proposed casting material consisting of a copper-zinc alloy, the proportion of the β phase in the sum of the α phase and the β phase is at least 20% by volume, preferably at least 35% by volume, and more preferably at least 40% by volume. A high proportion of the β phase has an adverse effect on ductility. Therefore, the proportion of the β phase is not more than 70% by volume, preferably not more than 60% by volume. The Si content of the alloy is 0.15% to 1.2% by weight, and the P content is 0.20% to 0.38% by weight. In addition, up to 0.25% by weight of Pb may be present, preferably up to 0.10% by weight of Pb. At the same time, the proportion of the β phase and the proportions of Si and P are selected so that the alloy satisfies the following conditions

[0032] 92.7249-0.473254·[β]-80.6378·[Si]-142.65·[P]+279.309·[Si]·[P]<40

[0033] Wherein, [β] denotes the proportion of the β phase in % by volume, [Si] denotes the proportion of silicon in % by weight, and [P] denotes the proportion of phosphorus in % by weight. This relationship quantitatively describes the influence of the parameters of the β phase, Si and P on the machining properties of the alloy, as well as the interaction of these parameters with one another. For example, it is thus possible, within the stated range of the alloy composition, to compensate for a small proportion of the β phase with a higher proportion of silicon and / or phosphorus, and vice versa.

[0034] The Cu content of the alloy is 58.0% to 66.0% by weight. In the case where the Cu content is less than 58.0% by weight, the ductility of the alloy is low. In the case where the Cu content is more than 66.0%, the zinc content in the alloy is too small to achieve good machinability.

[0035] Furthermore, the composition of the alloy may preferably be selected such that the Si / P ratio is at least 0.6, more preferably at least 0.9. In a further preferred embodiment, the composition of the alloy may be selected such that the sum of Si and P is at least 0.58% by weight, more preferably at least 0.64% by weight. The above measures contribute, both individually and in combination, to achieving the above relationship and, therefore, to achieving advantageous machining properties.

[0036] The optional elements Sn and Al promote the formation of the β phase. In the case of a Sn content of more than 0.5% by weight, additional tin-containing phases may be formed, which may have an adverse effect on the properties of the alloy. The proportion of tin should preferably not exceed 0.3% by weight, more preferably not exceed 0.2% by weight. In addition, aluminum forms aluminum phosphides with phosphorus. However, these are undesirable, and therefore the Al content should not exceed 0.05% by weight.

[0037] Iron leads to a grain refinement of the microstructure. In addition, iron forms hard phosphides and silicides, which have a negative effect on the service life and polishability of the tool during machining. Therefore, the proportion of iron must not exceed 0.3% by weight, preferably not more than 0.1% by weight.

[0038] Nickel promotes the formation of the alpha phase. In addition, nickel forms phosphides, which have no favorable effect on machinability. Therefore, the proportion of nickel must not exceed 0.3% by weight, preferably not more than 0.1% by weight.

[0039] The element Bi is present as an impurity in secondary raw materials, such as scrap. It can improve the machinability of the alloy. In an amount not exceeding 0.1% by weight, Bi has no adverse effect on the alloy. Therefore, up to 0.1% by weight of Bi in the alloy is tolerated. Preferably, the proportion of Bi is less than 0.015% by weight.

[0040] The elements Te, Se and In can have a favorable effect on the machinability of the alloy. In an amount not exceeding 0.1% by weight each, they have no adverse effect on the alloy. Therefore, up to 0.1% by weight of each Te, Se and In is tolerated in the alloy.

[0041] Optional proportions of up to 0.01% by weight of boron contribute to grain refinement.

[0042] The balance of the alloy composition consists of zinc and unavoidable impurity components. In order to avoid uncontrolled influence of impurities on the alloy properties, the proportion of these impurities does not exceed 0.2% by weight. In particular, the proportions of Mn and Mg should each be no more than 0.1% by weight, more preferably no more than 0.05% by weight, because these elements can form phosphides that can compete with phosphides containing copper and / or zinc.

[0043] In a preferred configuration of the invention, the Pb content in the alloy may be at least 0.02% by weight. Even such a small proportion of Pb improves the machining properties.

[0044] Advantageously, the weight ratio of P to the sum of Fe and Ni may be greater than 2.0, i.e., P / (Fe+Ni)>2.0. This achieves the effect of mainly forming copper-containing and / or zinc-containing phosphides that are advantageous for machining properties. The formation of iron phosphide or nickel phosphide is suppressed.

[0045] It may be particularly advantageous if the proportion of Fe and Ni combined does not exceed 0.1% by weight. This limitation also suppresses the formation of iron phosphides and nickel phosphides compared to the formation of copper and / or zinc-containing phosphides.

[0046] In a particularly advantageous embodiment of the invention, the P content can be at least 0.26% by weight and at most 0.33% by weight. If the P content is at least 0.26% by weight, a sufficiently large number of phosphide particles are formed to achieve particularly fine grains and very good machinability.

[0047] In an advantageous configuration of the invention, the Si content may be at least 0.50% by weight and at most 1.0% by weight. Casting materials consisting of copper-zinc alloys having Si contents within this range are distinguished by excellent machinability.

[0048] Another aspect of the present invention relates to a method for producing a cast product, wherein the method comprises the following steps:

[0049] a) melting a copper-zinc alloy having the composition as described above,

[0050] b) casting a cast product, and subsequently cooling the cast product, wherein the cooling rate in the temperature range of 550° C. to 350° C. is at least 20° C. / minute and at most 60° C. / minute.

[0051] The method can produce a cast product from the above-mentioned casting material consisting of a copper-zinc alloy. The alloy can be melted using a Cu cathode, a Zn block, brass scrap, a Cu-P pre-alloy and a Cu-Si pre-alloy. The melting is preferably achieved in an induction kiln. Subsequently, the melt is cast into a cast product. The cast product is cooled, wherein the cooling rate in the temperature range from 550°C to 350°C is at least 20°C / minute, preferably at least 30°C / minute, and at most 60°C / minute, preferably at most 50°C / minute. The defined cooling establishes a favorable ratio of the volume proportions of the α phase and the β phase to each other and a favorable particle distribution of the copper and / or zinc phosphide in the casting material of the cast product.

[0052] With regard to further technical features and advantages of the method according to the invention, reference is hereby explicitly made to the description and working examples in the context of the casting material according to the invention consisting of a copper-zinc alloy.

[0053] Another aspect of the present invention relates to a casting made of the above-mentioned casting material. A casting refers to a product whose material has not undergone further shaping after casting and cooling. The production of the casting is carried out by a casting product melted and cast by the above-mentioned method. The casting product is machined for molding purposes. In addition, at least a portion of the surface can be polished. Optionally, the casting is coated in whole or in part. Therefore, a casting is produced from the above-mentioned casting material or casting product by machining and optional additional processing steps. Such a casting can be, for example, a connector, a T-piece, a component of a valve, a faucet or a water pipe.

[0054] The present invention is illustrated in detail by means of working examples and comparative examples.

[0055] Samples No. 1 to No. 12 were melted in an induction kiln and then cast into small pieces in a mold. The cooling rate during solidification was 36°C / minute (°C / min) in the temperature range of 550°C to 350°C. The composition of the samples is recorded in Table 1. Sample No. 5 represents the leaded reference alloy CuZn39Pb1Al-B.

[0056] Transverse sections were taken from the ingots and these were used to examine the microstructure by optical microscopy. The reported volume fractions of α and β phases were normalized to the sum of α and β phases. The hardness HV was determined. The electrical conductivity was determined by the eddy current method using a probe.

[0057] The grain size of the beta grains is determined according to EN ISO 2624. This is done by drawing linear cuts in the transverse direction of the transverse slice (referred to as "vertically") and determining the number of cut beta grains along the linear cuts. The average linear cut length in the transverse direction corresponds to the average beta grain diameter in the transverse direction. Similarly, linear cuts are drawn in the thickness direction of the transverse slice (referred to as "horizontally") and the number of cut beta grains along these linear cuts is determined. The average linear cut length in the thickness direction corresponds to the average beta grain diameter in the thickness direction.

[0058] Optical microscopy images of unetched samples were used to quantitatively determine the size distribution of the phosphide particles. 2 The phosphide particles were classified by their equivalent diameter into 0.5 μm to 1 μm, 1 μm to 2 μm, 2 μm to 5 μm and, if present, into a category greater than 5 μm.

[0059] Machinability was determined by planing tests. This was done using indexable inserts with a profile that promotes chip breakage. The machining depth was 125 μm and the planing speed was 35 m / min. During the planing operation, the bending moment acting on the tool was measured and this was used to determine the average value of the bending moment. The resulting chips were visually assessed and classified by chip form. The chip form was assigned a chip form number according to the following list:

[0060] Crumb form number Crumb form 0 Torn debris, spiral debris 0.5 Curled 1 to 2 circles of rolled debris 0.75 The curling arc forms a rolled debris with an angle of 270° to 360° 1.0 The curling arc forms a rolled debris with an angle of 180° to 270° 1.25 The curling arc forms a rolled debris with an angle less than 180°

[0061] Chip form number 1.0 corresponds to the reference alloy CuZn39Pb1Al-B (sample number 5) containing 1% by weight of lead.

[0062] The machinability of the samples was evaluated using the bending moment determined in planing and the shape of the chips. An average bending moment of not more than 37 Nm and chips corresponding to chip form numbers 1.0 or 1.25 were evaluated as very favorable.

[0063] The results of the study are reported in Table 1. Sample No. 1 to No. 4 are samples of the present invention. Sample No. 5 to No. 12 are comparative samples and are marked with (*).

[0064] Furthermore, an attempt was made to parameterize the measured average bending moment as a function of the volume fraction of the β phase and the weight fraction of Si and P. The functional relationship thus determined can be expressed as follows:

[0065] f=92.7249-0.473254·[β]-80.6378·[Si]-142.65·[P]+279.309·[Si]·[P]

[0066] Wherein f approximately quantifies the measured bending moment in Nm, and where [β] denotes the proportion of β phase in volume %, [Si] denotes the proportion of silicon in weight %, and [P] denotes the proportion of phosphorus in weight %. The value of f calculated by this formula is reported in the last column of Table 1. The comparison of this value f with the measured bending moment shows a very good agreement between the two parameters (with the exception of the two samples No. 6 and No. 7, which have very poor machinability). The samples No. 1 to No. 4 of the invention, all of which have a measured bending moment of less than 37 Nm, are characterized by a value of f less than 40.

[0067] Table 1 Composition and structural characteristics of samples

[0068]

[0069]

[0070] Table 1 Composition and structural characteristics of samples (continued)

[0071]

[0072] Samples No. 1 to No. 4 are samples of the present invention. The volume of the β phase is at least 38%, and at most 57%. The β grain size is not more than 645 μm in the lateral direction ("vertically"), and not more than 781 μm in the thickness direction ("horizontally"). The ratio of the β grain size in the thickness direction to the β grain size in the lateral direction is not more than 1.21. Therefore, the grains have a topological structure without a preferred direction and are rated as spherical. The hardness is at least 110 HV10. The measured bending moment is not more than 36.5 Nm. The form of the debris of all samples corresponds to the debris form number 1.25. Therefore, the form of the debris is very favorable.

[0073] Samples No. 5 to No. 12 are comparative samples. Reference sample No. 5 contains 1.1% lead by weight and is characterized by very small grain size, very low bending moment and good chip form. Samples No. 6 and 7 contain only very small amounts of silicon and phosphorus in addition to copper and zinc. For both samples, the β grain size is very large, the bending moment measured during machining is high, and the chip form is poor.

[0074] Sample Nos. 8 to 11 each contain about 0.55% silicon by weight. Sample Nos. 8 and 10 contain no and only very little phosphorus, respectively, while Sample Nos. 9 and 11 contain phosphorus in amounts of 0.126% by weight and 0.067% by weight, respectively. In the case of Sample Nos. 10 and 11, the zinc content is slightly higher than that of Sample Nos. 8 and 9 by 1% by weight. The greater zinc content leads to a greater volume proportion of the β phase. Comparison of Sample Nos. 8 and 10 with Sample Nos. 6 and 7 shows that the inclusion of about 0.55% silicon by weight in the alloy significantly reduces the bending moment acting during machining due to the hardening of the α and β phases. In the case of Sample Nos. 6 and 7, the higher volume proportion of the β phase is greater than that compensated by the silicon content in the case of Sample Nos. 8 and 10. In addition, the bending moment also decreases with increasing P content. In the case of Sample Nos. 8 to 11, the chip form is favorable.

[0075] The β grain size in the case of sample numbers 8 to 11 is smaller than that in the case of sample numbers 6 and 7. The β grain size tends to decrease with increasing P content. On the other hand, the β grain size of sample numbers 8 to 11 is larger than that of sample numbers 1 to 4. In particular, in the case of sample numbers 8 to 11, the horizontal β grain size is larger than the vertical β grain size by more than 1.25 times, and usually even larger by more than 2.5 times, while in the case of sample numbers 1 to 4, the horizontal β grain size is larger than the vertical β grain size by at most 1.25 times.

[0076] Due to the phosphorus content of 0.276% by weight, sample No. 12 shows spherical β grains with a vertical β grain size of 605 μm and a horizontal β grain size of 856 μm. However, sample No. 12 has a proportion of β phase of only 22% by volume and a low Si content of 0.277% by weight, which means that the bending moment acting during machining increases and the condition is not satisfied, which is:

[0077] 92.7249-0.473254·[β]-80.6378·[Si]-142.65·[P]+279.309·[Si]·[P]<40

[0078] The f value calculated from the Si content, the P content and the volume fraction of the β phase is 42.0 and is therefore in good agreement with the measured bending moment of 42.5 Nm. A comparison of sample No. 12 with sample No. 4 having a similar composition shows that the low Si content must be compensated by a higher Zn content so that the cast material has a sufficient proportion of the β phase by volume and therefore has favorable machining properties. It is therefore necessary to select the alloy composition and the process scheme so that the above conditions are met in the interaction of these quantities and parameters. It is not sufficient to consider each of the quantities and parameters mentioned alone.

[0079] Samples No. 1 to No. 4 are noteworthy for grains with a topology without a preferred direction, i.e. for spherical grains, and with a β grain size of not more than 800 μm, while in the case of samples No. 8 to No. 11, the β grain size is in principle larger. In addition, in the case of samples No. 8, No. 10 and No. 11, the β grain size in the thickness direction (“horizontally”) is much larger than the β grain size in the transverse direction (“vertically”). Therefore, in the case of samples No. 8, No. 10 and No. 11, as in the case of samples No. 6 and No. 7, the grain form is described as columnar and is assessed as unfavorable. In the case of samples No. 1 to No. 4, the reason for the favorable topology and size of the grains is a phosphorus content of at least 0.24% by weight combined with a specifically selected cooling rate in the temperature range between 550° C. and 350° C. during solidification after casting. In the case of samples No. 1 to No. 4, the favorable topology and size of the grains firstly lead to good mold filling during casting and secondly to good polishability of these samples.

Claims

1. A casting material consisting of a copper-zinc alloy having the following components in wt %: Cu: 58.0% to 66.0%, Si: 0.15% to 1.2%, P: 0.20% to 0.38%, Sn: optionally, up to 0.5%, Al: optionally, up to 0.05%, Fe: optionally, up to 0.3%, Ni: optionally, up to 0.3%, Pb: optionally, up to 0.25%, Bi: optionally, up to 0.1%, Te, Se, In: each optionally, up to 0.1%, B: optionally, up to 0.01%, Balance: Zinc and unavoidable impurities, in, The proportion of unavoidable impurities is less than 0.2% by weight, The alloy has a microstructure consisting of α phase, β phase and phosphide particles, and the proportion of β phase in the sum of α phase and β phase is at least 20% by volume and at most 70% by volume, wherein silicon is present in both α phase and β phase, and at 21000 μm 2 In the area, there are 20 to 300 phosphide particles with an equivalent diameter of 0.5 μm to 1 μm, there are 30 to 120 phosphide particles with an equivalent diameter of 1 μm to 2 μm, and there are 20 to 100 phosphide particles with an equivalent diameter of 2 μm to 5 μm, and the proportion of the β phase and the proportion of Si and P are selected to meet the following conditions: 92.7249-0.473254·[β]-80.6378[Si]-142.65·[P]+279.309·[Si]·[P]<40 Here, [β] represents the proportion of the β phase by volume %, [Si] represents the proportion of silicon by weight %, and [P] represents the proportion of phosphorus by weight %.

2. The casting material composed of a copper-zinc alloy according to claim 1, characterized in that The lead content is at least 0.02% by weight.

3. The casting material composed of a copper-zinc alloy according to claim 1 or 2, characterized in that: The ratio of the weight proportion of phosphorus to the weight proportion of the sum of iron and nickel is greater than 2.

0.

4. The casting material composed of a copper-zinc alloy according to any one of claims 1 to 3, characterized in that The total proportion of iron and nickel shall not exceed 0.1% by weight.

5. The casting material composed of a copper-zinc alloy according to any one of claims 1 to 4, characterized in that The phosphorus content is at least 0.26% by weight and at most 0.33% by weight.

6. The casting material composed of a copper-zinc alloy according to any one of claims 1 to 5, characterized in that The Si content is at least 0.50% by weight and at most 1.0% by weight.

7. A method for producing a cast product, wherein: The method comprises the following steps: a) melting a copper-zinc alloy having a composition as claimed in any one of claims 1 to 6, b) casting a cast product, and subsequently cooling the cast product, wherein the cooling rate is at least 20°C and at most 60°C per minute in a temperature range of 550°C to 350°C.

8. A casting made from the casting material according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Lead-free free-cutting silicon brass alloy with high zinc and its manufacturing method

    EP2194150B1

  • Free-cutting copper alloy casting, and method for producing free-cutting copper alloy casting

    EP3992321A1

  • Brass, its manufacturing method, and part using the same

    JP2005290475A

  • Brass material superior in hot workability and machinability

    JP2006083443A

  • Lead-free free-cutting brass excellent in castability

    JP2014122427A